2017
DOI: 10.1017/s104161021700240x
|View full text |Cite
|
Sign up to set email alerts
|

Physical restraint to patients with dementia in acute physical care settings: effect of the financial incentive to acute care hospitals

Abstract: The financial incentive may have reduced the risk of physical restraint among patients with dementia in acute care hospitals. However, use of physical restraint was still common among patients with dementia in units with the dementia care benefit. An educational package to guide dementia care approach including the avoidance of physical restraint by healthcare professionals in acute care hospitals is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
3
30
1
1
Order By: Relevance
“…6,30 However, physical restraints should be avoided, wherever possible, in conformance with recommendations that have been issued worldwide, including in Japan. [14][15][16][17] We considered the following two major reasons for the increased use of physical restraints in elderly dementia patients compared with recent trends in the previous year: 1) patient factors and 2) factors associated with the care system.…”
Section: Discussionmentioning
confidence: 99%
“…6,30 However, physical restraints should be avoided, wherever possible, in conformance with recommendations that have been issued worldwide, including in Japan. [14][15][16][17] We considered the following two major reasons for the increased use of physical restraints in elderly dementia patients compared with recent trends in the previous year: 1) patient factors and 2) factors associated with the care system.…”
Section: Discussionmentioning
confidence: 99%
“…36 The use of physical and chemical restraints has not only shown to be ineffective but may result in adverse events for patients, caregivers, and staff, as well as regulatory challenges. 37,38 Figure 3. Frequency of constant observation use for selected conditions, percentage of respondents answering "often" or "very often" according to position.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of all public and private nursing homes in Malta, Fenech (2016) indicated that staff working in these homes reported a high observed incidence of physical restraints. Nakanishi, Okumura & Ogawa (2018), found that among patients with dementia admitted to acute hospitals, the point prevalence of physical restraints was as high as 44.5%. This high prevalence has been attributed to the priority given by hospital staff perceptions around patient safety and risks associated with 'wandering' or falls, at the expense of the patient's esteem needs for dignity and autonomy (Digby, Lee & Williams, 2017).…”
Section: Discussionmentioning
confidence: 99%